2018
DOI: 10.1111/psyp.13206
|View full text |Cite
|
Sign up to set email alerts
|

Event‐related potentials to threat of predictable and unpredictable shock

Abstract: Cognitive affective neuroscience tasks that are straightforward to administer, measure key constructs of interest, and can be used in different lab settings and with multiple psychophysiological methods can lead to a more complete understanding of experimental effects. The no-threat, predictable threat, unpredictable threat (NPU-threat) task assesses constructs of interest to both clinical and basic affective science literatures, is relatively brief to administer, and has been used across labs with a number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 51 publications
3
33
0
Order By: Relevance
“…Research also suggests that, compared to relatively more predictable threats, less predictable threats can be particularly aversive and as such associated with greater defensive responding, as measured by fear potentiated startle (Schmitz & Grillon, 2012). In accordance with previous literatures, we expected the unpredictable threat condition, relative to predictable and no-threat conditions, to increase defensive responding (startle potentiation; Baas, Kenemans, Böcker, & Verbaten, 2002;Bennet, Dickmann, & Larson, 2018;MacNamara & Barley, 2018) and lead to greater disruptions in neurocognitive indicators of cognitive control (i.e., reduced congruence N2 and P3) across participants. Similarly, we also expected that the unpredictable threat condition would be associated with the poorest performance on behavioral indicators of cognitive control (slower RT and decreased accuracy) in the flanker task (Fan, McCandliss, Sommer, Raz, & Posner, 2002).…”
Section: Proposed Studysupporting
confidence: 83%
“…Research also suggests that, compared to relatively more predictable threats, less predictable threats can be particularly aversive and as such associated with greater defensive responding, as measured by fear potentiated startle (Schmitz & Grillon, 2012). In accordance with previous literatures, we expected the unpredictable threat condition, relative to predictable and no-threat conditions, to increase defensive responding (startle potentiation; Baas, Kenemans, Böcker, & Verbaten, 2002;Bennet, Dickmann, & Larson, 2018;MacNamara & Barley, 2018) and lead to greater disruptions in neurocognitive indicators of cognitive control (i.e., reduced congruence N2 and P3) across participants. Similarly, we also expected that the unpredictable threat condition would be associated with the poorest performance on behavioral indicators of cognitive control (slower RT and decreased accuracy) in the flanker task (Fan, McCandliss, Sommer, Raz, & Posner, 2002).…”
Section: Proposed Studysupporting
confidence: 83%
“…As in previous research, we predicted that an instructed threat context would be rated as more unpleasant, arousing, and threatening compared to the safety condition (Bublatzky et al, 2010(Bublatzky et al, , 2014Costa et al, 2015). On the neural level, we expected enhanced late positive potentials to instructed threat compared to safety conditions over parieto-occipital visual processing areas as indicators for selective attention and elaborate stimulus 10.3389/fnbeh.2022.908454 processing (Bublatzky and Schupp, 2012;MacNamara and Barley, 2018).…”
Section: Introductionmentioning
confidence: 75%
“…Across both lab sites, we observed a lack of IU-related effects for the orbicularis oculi measure during the instructed uncertain threat tasks. Previous research has reported extensive variability in IU-related profiles for the orbicularis oculi measure during instructed uncertain threat tasks (Gorka et al, 2014;Morriss, Bennett, et al, 2021;Morriss et al, 2020;Nelson et al, 2016;Nelson & Shankman, 2011), including null effects (MacNamara & Barley, 2018;Mertens & Morriss, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, a recent review (Tanovic, Gee, et al, 2018) highlighted that there were mixed findings for how IU modulates anticipatory physiological responses during instructed uncertain threat (typically also referred to as risk, irreducible uncertainty, first-order uncertainty, expected uncertainty (Angela & Dayan, 2005;Kobayashi & Hsu, 2017)). For example, during tasks where participants are instructed about the (un)predictability of aversive stimuli such as electric shocks or negative pictures, some psychophysiology studies report IU-related effects (Gorka, Lieberman, Nelson, Sarapas, & Shankman, 2014;Morriss, Bell, Biagi, Johnstone, & van Reekum, 2021;Morriss, Bennett, & Larson, 2021;Morriss et al, 2020;Nelson, Liu, Sarapas, & Shankman, 2016;Nelson & Shankman, 2011;Somerville et al, 2013;Tanovic, Pruessner, & Joormann, 2018), while others do not (Grupe & Nitschke, 2011;MacNamara & Barley, 2018;Mertens & Morriss, 2021;Morriss, 2019;Morriss, Bell, et al, 2021). Furthermore, IU-related effects in instructed uncertain threat tasks vary considerably within and across physiological measures.…”
Section: Introductionmentioning
confidence: 99%